“Feeling -The -Rice- Bag” Sign: A Pathognomonic Manifestation of Synovial Osteochondromatosis - Phúc, Lê (Clinical Medicine And Health Research Journal, 2023)
Synovial Osteochondromatosis is not rare in joint pathology.An orthopaedic surgeon may have around 30 cases in life career. The inner surface of synovium is presumably affected by inflammatory process and forms the osteochondral body. By the time this osteochondral formation detaches from synovium and becomes loose body in the joint. Synovial Osteochondromatosis is a pathological status in which there are multiple loose bodies inside the joint. Synovial Osteochondromatosis is presumably a benign disorder, but whose common complication is blockade of joint when loose body incacerated between cartilages of joint causing acute pain and joint cannot move.In medical terminology there is Osteochondromatosis who is a different pathology, a kind of benign bone tumors, not the title of this article. Multiple loose bodies can be detected by Feeling- the- Rice- Bag Sign. Place the hand over the involved joint, we can feel the loose bodies as if we feel the rice grain in the bag. More loose bodies exist, easier we feel. More superficial the joint and/or loose bodies are , easier feeling is recognized.Feeling -the -Rice- Bag Sign is pathognomonic manifestation for the Synovial Osteochondromatosis.